3D‐AJP: Fabrication of Advanced Microarchitected Multimaterial Ceramic Structures via Binder‐Free and Auxiliary‐Free Aerosol Jet 3D Nanoprinting - Chunshan Hu; Sanjida Jahan; Bin Yuan; Rahul Panat (Advanced Science)
Abstract Manufacturing of ceramics is challenging due to their low toughness and high hardness. Additive Manufacturing (AM) has been explored to create complex ceramic structures, but current techniques face a tradeoff between precisely controlled feature sizes and high shrinkage at the microscales. Here, we introduce 3D‐AJP, a novel freeform ceramic fabrication method that enables highly complex microscale 3D ceramic architectures—such as micropillars, spirals, and lattices—with minimal shrinkage and no auxiliary support. Using a near‐binder‐free nanoparticle ink in an Aerosol Jet (AJ) 3D printer, our approach precisely controls feature sizes down to 20 µm with aspect ratios up to 30:1. The resulting structures exhibit exceptionally low linear shrinkage of 2‐6% upon sintering, spanning five orders of magnitude in length scale. Bi‐material 3D architectures (zinc oxide/zirconia, zinc oxide/titania, titania/zirconia) and hybrid ceramics further demonstrate the technique’s versatility. We showcase two key applications. First, 3D ceramic photocatalysts improve water purification performance, achieving a 400% increase in photocatalytic efficiency compared to bulk ceramics. Second, we develop a highly sensitive Her2 biomarker sensor for breast cancer detection, achieving a 22‐second response time and a record‐low detection limit of 0.0193 fm. Our technique will lead to high‐performance sensing, filtration, microelectronics packaging, catalysis, and tissue regeneration technologies.